PARTISIPASI MASYARAKAT DALAM MENGATASI MASALAH PENDIDIKAN DI KABUPATEN PANDEGLANG BANTEN - Fatimah, Farah (Peneliti.net, 2023)
Community participation in overcoming education problems in the Pandeglang district of Banten. Mentor. The problem of education in Banten's Pandeglang Regency is not new. The level of education that still lacks makes the thinking of the public less open. Many parents consider education not too important. The causes of this education problem are many because of the lack of facilities provided, starting from school buildings, teachers etc. The Pandeglang Banten District Education Office has tried to improve the quality of education in all sub-districts included in Banten's Pandeglang Regency by implementing various kinds of policies. This type of research uses a qualitative approach with descriptive methods. Whereas the research location was in the Village Education Unit of Menes, Pandeglang Banten Regency and the surrounding community. From the above research, it can be obtained from Menes Village community participation in overcoming the problem of Education in Pandeglang Banten Regency and what kind of community participation.